Rethinking Spiritual Assessment: Spiritual Assessment Interpretive Framework (SAIF) – Four Minimally Directive Questions - Nolan, Steve (Health and Social Care Chaplaincy, 2024)
Spiritual assessment is a core competence of professional spiritual care and can be understood to be a process of evaluating and addressing patients’ spiritual needs and resources in clinical healthcare contexts. A critical review of five recent (post-2010) spiritual assessment models reveals key design weaknesses. This article presents the Spiritual Assessment Interpretive Framework (SAIF), a pluralistic, constructivist and conceptually coherent model. From a research-based definition of spirituality and the perspective that patients narrate their spiritual state in their stories about their relation to self, to significant others, to their natural and sociopolitical environments, and to their beliefs and values, SAIF provides a framework of four minimally directive questions within which chaplains can interpret patients’ spiritual state and formulate assessments of their spiritual needs.